Comparative organoleptic examination of apple varieties developed by different environmentally safe technologies - Dremák, P. (International Journal of Horticultural Science, 2009)
Ecological or biological growing techniques are generally recognised as actual trends in agricultural production. The objective of our experiments is a comparison of apple fruits grown alternatively by integrated versus ecological technology. In a collection of varieties, the possibility of the experiment was feasible. At the same time, a comparison of the popularity of existing varieties was also actual. The organoleptic consumer’s tests rated the varieties, and the comparison with instrumentally raised “objective” data could be compared with the subjective ratings, which did not coincide with each other. This phenomenon was revealed in the rating of acid-sugar harmony, where the internationally used quality index of Thiault produced a different range of the samples then the consumer’s test. The same contradiction was observed between ratings of firmness and the data raised by penetrometer.